Factors Affecting Consumer Purchase Decisions for - Eso Hernawan Hernawan; Suhendar Janamarta; Hendra Hendra (eCo-Fin, 2019)
The purpose of writing this research is to determine the extent to which the factors that influence consumer purchasing decisions for Company. The research method used is through interviews and distributing questionnaires to respondents who are interested in Residence housing, as well as a literature review which is used as secondary data. For the analysis of this research the author uses quantitative and qualitative analysis methods. From the results of multiple linear analysis obtained Y = 2.657 + 0.655 X1 + 0.305 X2, meaning that if there is an increase or decrease in X1 and X2 variables, consumer purchasing decisions will increase or decrease by 0.655 and 0.305. From the results of the analysis of the price coefficient has a positive and strong correlation to consumer purchasing decisions that is equal to 0.895 and location has a positive and strong correlation to consumer purchasing decisions 0.924. From the results of the coefficient of determination (KD) the price affects consumer purchasing decisions by 80.1%, the remaining 50.3% is influenced by other factors and location affects consumer purchasing decisions by 85.4%, the remaining 14.6% is influenced by other factors. Based on the results of hypothesis testing, it is obtained that tcount for the price is 6.016 and tcount for the location is 5.939 which is obtained from the distribution ttable for df = 100 – 2 and the level of significance is 0.05. In other words Ho is rejected and Ha is accepted, because t count > t table